The Da Vinci Code [videorecording (DVD)] - Goldsman, Akiva; Hanks, Tom; Tautou, Audrey, 1976-; McKellen, Ian; Molina, Alfred, 1953-; Bettany, Paul, 1971-; Brown, Dan, 1964- (Sony Pictures Home Entertainment, 2006)
When respected American religious symbology expert Dr. Robert Langdon is summoned to the Louvre by French Captain Bezu Fache, he soon discovered that he is the number 1 suspect for the murder of a historian Langdon had been scheduled to meet with. Assisted by a French cryptographer and government agent named Sophie, Langdon is challenged to decipher a chain of cryptic codes and puzzles, all the while trying to stay ahead of Fache's lawmen in a chase through the Louvre, and out into the Parisian cityscape, and finally across the channel to England.